RESOLUSI KONFLIK DALAM PENGELOLAAN TAMAN NASIONAL LORE LINDU - Maiwa, Arman; Umar, Syukur; Golar, .; Rahman, Abdul (Universitas Tadulako)
Lore Lindu National park (TNLL) plays significant roles on ecosystem protection and biodiversity supporting system of such kind of floras and faunas. The aims of this study are: 1) to identify the conflicts in TNLL, 2) to identify the roles of stakeholders, and 3) to arrange the collaborative programs as an effort of conflict resolution in TNLL. The study had been done in Dongi â Dongi village of TNLL. There are three methods of analysis has applied for this study i.e., spatial analysis method, stakeholder ansysis (4 Rs), and descriptive analysis. According to Ministry of Forestry Decree No. 464/Kpts-II/1999, July 23rd 1999, the total area of TNLL is 217.991,18 ha. Based on the study the land occupancy increase from 3.078,86 ha (1,41%) to 3.299,74 (1,51%) in 2010 and became 3.840,64 ha (1,74%) in 2014. The study has also identified the stakeholders who are involved in management of Dongi âDongi such as BBTNLL, BPKH, BPDAS, Local Government, FPM, Community, NGOs, and Universities. It can be concluded that collaborative management of TNLL is the most reasonable resolution to resolve the conflict in Dongi â Dongi.Â Keywords: Resolution, Collaboration, Lore Lindu National Park